2009
DOI: 10.1177/216507990905700606
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Back Pain among Farm Women in Southeast Louisiana

Abstract: This cross-sectional survey details the incidence and predictors of self-reported back pain among farm women from southeastern Louisiana. The sample was obtained from a preexisting data set of a cross-sectional randomized sample of farm women who participated in the Louisiana Farm Family Injury Prevention and Health Initiative research project. The Haddon Injury Model was used as the conceptual framework. Approximately one fourth of the women in the sample reported back pain in the past year. The major finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although few studies 20 have found no significant differences in the prevalence of LBP between genders, the present study found that LBP was higher in women (67.7%) compared with men (51.6%). It was found in 2 studies 21,22 that LBP symptoms were consistently more common among women. Women continue to be the primary informal caregivers for the majority of children and older people in Asian countries and this too is a factor in women’s back pain syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few studies 20 have found no significant differences in the prevalence of LBP between genders, the present study found that LBP was higher in women (67.7%) compared with men (51.6%). It was found in 2 studies 21,22 that LBP symptoms were consistently more common among women. Women continue to be the primary informal caregivers for the majority of children and older people in Asian countries and this too is a factor in women’s back pain syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Women continue to be the primary informal caregivers for the majority of children and older people in Asian countries and this too is a factor in women’s back pain syndromes. Hathorn et al 22 stated that the risk of LBP is higher among women because of the stress of hormonal changes, gynecological problems, and childbirth.…”
Section: Discussionmentioning
confidence: 99%